ANALISIS DINAMIS PENGARUH INDIKATOR MAKROEKONOMI TERHADAP KAPITALISASI PASAR JAKARTA ISLAMIC INDEX (JII): PENDEKATAN ERROR CORRECTION MODEL (ECM) - Pramono, Sigit; Khasanah , Titi Nur; Abdul Adhim (PT. Media Edutama Nusantara, 2025)
The purpose of this study is to examine how the market capitalization of the Jakarta Islamic Index (JII) was affected by inflation, the BI 7-Day Reverse Repo Rate (BI7DRR), and the currency rate between January 2016 and December 2024. The Financial Services Authority (OJK) and Bank Indonesia (BI) are the sources of secondary data used in this study. The Error Correction Model (ECM), an analytical technique that may detect both short-term and long-term associations as well as the process of adjustment towards market equilibrium, is employed. The findings indicate that while the exchange rate has a negligible short-term impact on JII market capitalization, it has a favorable and large long-term impact. Although not in the short term, the BI7DRR interest rate has a favorable and noteworthy impact over the long run. In the meantime, there is no discernible short- or long-term impact of inflation on JII market capitalization. These results highlight how crucial interest rate policy and currency rate stability are to fostering the growth of Indonesia's Islamic capital market.